Effects of ice hockey facial protectors on response time - Dowler, P. M.; Pearsall, D. J. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
While the added protection given to ice hockey players through the use of visors and cages has been well documented (Benson et al., 2002; Stevens et al., 2006; Lemair & Pearsall, 2007), a perception in the hockey community remains that cages and visors impair the field of vision, and in turn delay response time and subsequent movements. In ice hockey, a fast paced sport that heavily relies on vision and reaction time, any impairment in the field of vision has the potential to lower one`s level of play. Furthermore, a slight latency in one`s response time could have effects on both performance and safety on the ice. Some prior studies examining the effects of visors and sports goggles on visual function do report a reduction in peripheral vision (Ing et al., 2002). However, no studies have addressed the subsequent effects on movement response time. This forms the basis for the current study.